The Engagement Interview Protocol (EIP): improving the acceptance of mental health treatment among Chinese immigrants - Yeung, Albert (2011)
Many depressed Chinese immigrants are unfamiliar with Western psychiatric terminology and have high levels of stigma toward psychiatric illnesses, making it difficult to engage them into psychiatric treatment. We have designed the Engagement Interview Protocol (EIP), a semi-standardized protocol that incorporates cultural components to a standard psychiatric evaluation. The EIP elicits patients’ narratives and uses anthropological questions to explore patients’ illness beliefs, which are integrated with patients’ information on medical and psychiatric history, psychosocial background and mental status examination so that treatment options can be negotiated in a culturally sensitive manner. In our field testing on depressed Chinese immigrants, the EIP model was found to be a practical tool that can be completed within the allotted one-hour time frame and was highly effective in facilitating the enrollment of patients in treatment for depression. The EIP is a concise, time-effective, user-friendly protocol that can be used both in research and real-world clinical settings with diverse patient populations.